The Impact of Obesity on Intraoperative Complications and Prolapse Recurrence After Minimally Invasive Sacrocolpopexy. Issue 5 (September 2016) - Turner, Lindsay; Lavelle, Erin; Lowder, Jerry L.; Shepherd, Jonathan P.
Abstract : Objective: Our objective was to compare the risk of intraoperative complications and prolapse recurrence among normal-weight, overweight, and obese women after minimally invasive sacrocolpopexy. Methods: This is a retrospective study of all laparoscopic and robotic sacrocolpopexies performed at a large academic center from 2009 to 2014. Patient demographics and clinical and surgical data were compared between normal-weight, overweight, and obese women using χ 2 test, analysis of variance (ANOVA), and logistic regression. Results: Of the 556 subjects, 187 (33.6%) were normal weight, 248 (44.6%) were overweight, and 121 (21.8%) were obese. Compared with normal-weight and overweight women, obese women had more medical comorbidities (56.2% vs 29.4% and 39.5%, P < 0.001) and were more likely to undergo robotic surgery (odds ratio, 1.40; 95% confidence interval, 1.01–1.94). Obese women experienced greater blood loss compared with overweight women (82.4 [76.1] vs 63.8 [51.6] mL, P = 0.03) and longer operative times compared with both normal-weight and overweight women (250.7 [57.0] vs 233.8 [58.2] minutes, P = 0.04, and 250.7 [57.0] vs 233.8 [57.2] minutes, P = 0.03). Obesity was a significant predictor of intraoperative complications even after correcting for surgeon experience, estimated blood loss, and concomitant hysterectomy (adjusted odds ratio, 3.42; 95% confidence interval, 1.21-9.70). Few women (7.6%) experienced recurrence of prolapse. Obesity was not a significant predictor of prolapse recurrence. Conclusions: In women undergoing minimally invasive sacrocolpopexy, obesity is associated with increased blood loss, longer operative times, and more intraoperative complications, specifically conversions to laparotomy. Even after correcting for blood loss, surgeon experience, and concomitant hysterectomy, obese women were 3 times as likely to have an intraoperative complication. Our data did not show that obesity was associated with increased risk of prolapse recurrence; however, postoperative follow-up was limited. Abstract : In women undergoing minimally invasive sacrocolpopexy, obesity is associated with increased blood loss, longer operative times and more intraoperative complications, specifically conversions to laparotomy.